2017
DOI: 10.18203/2394-6040.ijcmph20173345
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude of men towards sex determination and PCPNDT act in the field practice area of a medical college in coastal Karnataka

Abstract: Background: Usage of modern sophisticated diagnostic techniques for sex determination and preconception sex selection has been attributed to sex selective abortions and thus, may be a major contributor in decline of sex ratio.Methods: A cross-sectional study was conducted amongst married male patients attending OPDs of Rural Health Centres of K S Hegde Medical Academy over a period of 3 months (July 2016–September 2016) using a semi-structured and validated questionnaire which contained information on demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In our study, 42.6% of the respondents were aware of prenatal methods of sex determination which is similar to the findings obtained by Roy A and Biswas R in rural Darjeeling. 27 Another study conducted by Mahaur G et al in coastal Karnataka 28 showed that 62% of their respondents were aware of the same. None of the respondents in our study were aware about the gender before the birth of the child.…”
Section: Discussionmentioning
confidence: 98%
“…In our study, 42.6% of the respondents were aware of prenatal methods of sex determination which is similar to the findings obtained by Roy A and Biswas R in rural Darjeeling. 27 Another study conducted by Mahaur G et al in coastal Karnataka 28 showed that 62% of their respondents were aware of the same. None of the respondents in our study were aware about the gender before the birth of the child.…”
Section: Discussionmentioning
confidence: 98%